The influence of tennis court surfaces on player perceptions and biomechanical response - Starbuck, C.; Damm, L.; Clarke, K.; Carré, M.; Capel-Davis, J.; Miller, S.; Stiles, V.; Dixon, S. (Journal of Sports Sciences, 2016)
This study aimed to examine player perceptions and biomechanical responses to tennis surfaces and to evaluate the influence of prior clay court experience. Two groups with different clay experiences (experience group, n = 5 and low-experience group, n = 5) performed a 180° turning movement. Three-dimensional ankle and knee movements (50 Hz), plantar pressure of the turning step (100 Hz) and perception data (visual analogue scale questionnaire) were collected for two tennis courts (acrylic and clay). Greater initial knee flexion (acrylic 20. 8 ± 11.2° and clay 32.5 ± 9.4°) and a more upright position were reported on the clay compared to the acrylic court (P < 0.05). This suggests adaptations to increase player stability on clay. Greater hallux pressures and lower midfoot pressures were observed on the clay court, allowing for sliding whilst providing grip at the forefoot. Players with prior clay court experience exhibited later peak knee flexion compared to those with low experience. All participants perceived the differences in surface properties between courts and thus responded appropriately to these differences. The level of previous clay court experience did not influence players` perceptions of the surfaces; however, those with greater clay court experience may reduce injury risk as a result of reduced loading through later peak knee flexion.